Virtual Field Trips: Using Information Technology to Create an Integrated Science Learning Environment - Nix, Rebekah Kincaid (Curtin University, 2003)
This study evaluated a new Integrated Science Learning Environment (ISLE) that bridged the gaps between the traditionally separate classroom, field trip, and information technology milieus. The ISLE model involves a multi-faceted design to address the three basic forms of learning: acquisition of knowledge, change in emotions or feelings, and gain in physical or motor actions or performance. A holistic approach to teaching at the university level encompassed a step-wise, cumulative strategy that reinforced all scales of the Constructivist Learning Environment Survey (Personal Relevance, Uncertainty of Science, Shared Control, Critical Voice, and Student Negotiation) and minimised the potentially detrimental effects of information overload and non-linear processing. By addressing individuals and recognising limitations, the same conceptual and logistical frameworks were applied to teachers and to students uniformly in the classroom and in the field. This key factor of the ISLE program broadened all participants’ horizons and enabled them to see their role within the ‘big picture’. Thus, the common elements (knowledge) and basic components (understanding) in each realm became evident and the power of transfer for both content and concept was realised. A process approach to information technology provided a logical and meaningful mechanism for continuously scaling the program perspective from the classroom setting to the unique global environment of the World Wide Web. The final product of the ISLE program (virtual field trip) was constructed by linking the elements common to the supporting learning environments (university classroom, field trip, and information technology) at their basic levels: newness, massiveness, and appropriateness.A combination of qualitative methods and quantitative measures provided insight into the field trip milieu and evaluation of the near- and far-term effects of exposure to constructivist pedagogy answering the general question of whether changing teachers’ learning environments might affect a change in their respective students’ learning environments. Quantitative assessment through learning environment dimensions, attitude scales, and concept map analyses was supported by qualitative data derived from reflective field journals, interviews, and observations to investigate the impact of the emergent model. Data were collected from classroom teachers and their students to assess the impact of the ISLE program in terms of promoting a constructivist classroom learning environment, teachers’ attitudes toward information technology, and teachers’ conceptual development. School teacher and student subgroups were compared in terms of the teachers’ university/field trip program experience and content background. To this end, three new versions of the Constructivist Learning Environment Survey (CLES) were shown to be valid and useful in secondary schools and graduate university courses in Texas. Data from 1079 students in 59 classes in north Texas were subjected to principal components factor analysis confirmed the factor structure, internal consistency reliability, discriminant validity, and the ability to distinguish between different classes and groups for the comparative student form (CLES-CS). Descriptive statistics supported the usefulness of the comparative teacher (CLES-CT) and adult (CLES-A) forms. Administration of these versions of the same instrument was used to characterise the learning environment of the ISLE university/field trip program, as well as the public/private school classrooms.Further analysis and interpretation of these data suggest that the ISLE program was effective in terms of the degree of implementation of constructivist teaching approaches in the teachers’ school classrooms as assessed by teachers’ perceptions of the learning environment of their current classroom environment relative to other classes taught by them previously and students’ perceptions of the learning environment of their classroom environment relative to classes taught by other teachers in their school classrooms. Additional data suggest that the ISLE program was effective in terms of teachers’ perceptions of the university/field trip learning environment; changes in teachers’ attitudes to information technology; and teachers’ conceptual development. When an ANOVA was used to compare students’ perceptions of THIS and OTHER classes, statistically significant differences were found for some CLES scales. In particular, students whose teachers had attended the ISLE program (THIS) perceived higher levels of Personal Relevance and Uncertainty of Science in their classrooms relative to the classrooms of other teachers in the same schools (OTHER). From a practical point of view, this study documents a new model for improving learning and understanding in the field of education, specifically science education. Participation in the ISLE program provided a tangible opportunity for teachers to gain organised knowledge to make practical changes in their school classrooms. From a research point of view, this study makes a unique contribution to the field of learning environments by evaluating a comprehensive professional development program that used information technology to initiate teacher change from the central perspective of the learning environment.Development and validation of the CLES-CS contributes to a useful range of instruments for a variety of classroom contexts within the burgeoning field of learning environments research. The real world is where theory and practice come together and science becomes relevant, making sense that leads to understanding. The conceptual and logistical frameworks of the ISLE model seamlessly merged theory and practice with science and education through effective applications of information technology to create a rich learning environment. Virtual field trips, based on the ISLE model, can enable the principles of student-centred inquiry and constructivism to be practised for the benefit of all styles and ages of lifelong learners.